2021
DOI: 10.1002/onco.13684
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pooled Safety Analysis of Palbociclib in Combination with Endocrine Therapy for Hormone Receptor-Positive/Human Epidermal Growth Factor Receptor 2-Negative Advanced Breast Cancer: Updated Analysis with up to 5 Years of Follow-Up

Abstract: Background Previous studies demonstrated the tolerability of palbociclib plus endocrine therapy (ET). This analysis evaluated safety based on more recent cutoff dates and a longer palbociclib treatment exposure. Patients and Methods Data were pooled from three randomized studies of patients with hormone receptor‐positive/human epidermal growth factor receptor 2‐negative (HR+/HER2−) advanced breast cancer (ABC), including postmenopausal women who had not received prior systemic treatment for advanced disease (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…Given that there were no new safety signals observed in patients with preexisting conditions, it is perhaps unsurprising that palbociclib dose modifications were similar across preexisting condition subgroups. In the overall PALOMA-2 population, 39.4 % of patients receiving palbociclib plus letrozole experienced a dose reduction [ 13 ]. This is similar to the rates of palbociclib dose reduction in each of the preexisting condition subgroups reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Given that there were no new safety signals observed in patients with preexisting conditions, it is perhaps unsurprising that palbociclib dose modifications were similar across preexisting condition subgroups. In the overall PALOMA-2 population, 39.4 % of patients receiving palbociclib plus letrozole experienced a dose reduction [ 13 ]. This is similar to the rates of palbociclib dose reduction in each of the preexisting condition subgroups reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to PALOMA-2 and PALOMA-3, commonly reported AEs in real-world studies included neutropenia, other hematologic AEs, and fatigue [48,49,52]. Of note, interstitial lung disease was also observed with CDK4/6 inhibitors in the real-world setting as well as PALOMA studies [27,53]. Additionally, real-world data were utilized to expand the approved indications of palbociclib to include male patients with ABC in 2019 [54].…”
Section: Real-world Evidence Regarding Treatment With Palbociclibmentioning
confidence: 99%
“…In PALOMA-3, among patients in the palbociclib plus fulvestrant group, 53.3% experienced grade 3 and 8.7% experienced grade 4 neutropenia; febrile neutropenia was reported in 0.6% of patients [ 17 ]. A pooled analysis of data from the PALOMA-1, -2, and -3 trials showed that interstitial lung disease was reported in 1.5% of patients receiving palbociclib plus endocrine therapy and that the incidence of interstitial lung disease was similar across geographic locations [ 27 ]. Additionally, quality of life was maintained in patients treated with palbociclib plus endocrine therapy [ 28 , 29 ].…”
Section: Review Of Palbociclib Clinical Trial Datamentioning
confidence: 99%
“…[5] The PFS and toxicity analysis results are consistent with other reports of routine clinical practice, that is, real-world evidence from India and other countries and the global clinical trials. [6][7][8][9][10][11][12][13][14][15][16][17] The observed OS is lower than reported in real-world studies and clinical trials. Our analysis suggests that patients who were less heavily pre-treated had better outcomes.…”
Section: Discussionmentioning
confidence: 99%